Hepatitis A Outbreak Among Men Who Have Sex With Men, Yokohama, Japan, January to May 2018. Issue 3 (March 2019) - Yoshimura, Yukihiro; Horiuchi, Hiroshi; Sawaki, Kenji; Miyata, Nobuyuki; Kumazaki, Makoto; Usuku, Shuzo; Tachikawa, Natsuo
Abstract : Abstract: Between January and May in 2018, 17 male cases of hepatitis A were reported in Yokohama, Japan. Of these, 14 identified as men who have sex with men. The viral sequence in this outbreak was same as that of the recent European and Taiwanese outbreaks strain. Abstract : In early 2018, a hepatitis A virus outbreak occurred mostly among men who have sex with men in Yokohama, and the viral strains matched with those of the international outbreak.